VD_FINDINFO Décision / 2012 / 412 vom 22. Mai 2012 - VD Tribunal cantonal (2012)
INFIRMITÉ CONGÉNITALE, RECONSIDÉRATION, RADIATION DU RÔLE | 13 LAI, 53 al. 3 LPGA, 59 LPGA, 70 al. 2 let. a LPGA, 94 al. 1 let. c LPA-VD